IRAN-ISRAEL SALING SERANG HARGA MINYAK MENTAH MERANGKAK NAIK DAMPAKNYA TERHADAP EKONOMI RI - Karso, A. Junaedi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The shock of the conflict resurfaced after the Israeli military attacked Iran. The Iranian government is considering closing the Strait of Hormuz. The strait is the main route for shipping oil to and from the Persian Gulf.